METHODICAL PRINCIPLES OF ANTROPOGENIC TRANSFORMATION STUDY OF ENVIRONMENT (ON AN EXAMPLE OF KUPIANSK DISTRICT, KHARKIV REGION) - Бережний, Віталій (Human Geography Journal, 2014)
The article is devoted to land use study and the level of anthropogenic transformation of environment at the local level within the territory of small rivers basins. The paper discusses the following base definitions: “antropogenic territorial complex”, “anthropization”. Some approaches to use the area ratios between different cultural landscapes as a data sources for quality assessments of environment state are discussed. It is shown that besides the quantitative characteristics of natural and cultural territorial complexes, significant role must be taken for topological properties of land use types. Using of watersheds as a territorial basis for environment anthropogenic transformation study and some GIS-methods to realize the similar tasks are suggested in the article. The results of anthropization coefficient zonal statistic calculation and land use types variety within the territory of the region are also given in the article. The attention is paid to the socio-economic context and the significance of such studies in human geography.